Semantic Modifications in Selected English Words borrowed in Majhi Dialect of Punjabi - Anjum, Jamshaid; Hassan, Saqlain (Pakistan Languages and Humanities Review, 2024)
The study aims to explicate any changes that take place when the English borrowed in words in the Majhi dialect of Punjabi are used by the native speakers of the dialect. Also, the study aims to elucidate the types of changes that take place during the process of borrowing in the Majhi Dialect of Punjabi. This study tis significant to find the types of semantic changes which take place during the borrowing of English words used by the native speakers of the Majhi dialect of Punjabi there by affecting the sematic range of the words of donor language. The research is both qualitative and quantitative. The data for this research has been collected through interviews of the 8 monolingual native speakers with equal number of both male and female participants with primary education. Bloomfield’s framework of borrowing is applied in order to observe certain types of semantic changes. The results of study show that different types of changes take place during the borrowing process. Borrowing facilitates the native speakers at the cost of the donor language.